The "honeymoon" and protests in the first seven months of Rodrigo Chaves Roble's administration (May-December 2022) - Cortés Sequeira, Sofía (2023)
Using the methodology of the Analysis of Protest Events (AEP) and the Theory of Political Opportunities, this article carries out a descriptive analysis of the collective actions registered during the first seven months of the presidency of Rodrigo Chaves Robles in Costa Rica. Particularly, it discusses how social protest behaves in the context of political "honeymoons", that is, in the period early in the presidency in which there are high levels of presidential approval. The article concludes that the beginning of the Chaves Robles administration has been the least conflictive of the last eight years, which could be due to fewer political opportunities for social protest and the organization of political discontent in this period. However, Chaves’s first concrete government measures, especially those against labor rights and detrimental to public institutions, have gradually contributed to a gradual upturn in social protest, especially between August and October 2022.